IMPROVEMENT OF TEACHER’S ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH TRANSFORMATIONAL LEADERSHIP DEVELOPMENT AND INTERPERSONAL COMMUNICATIONS - Nunung Nuryani; Nandang Hidayat; Henny Suharyati (UNIVERSITAS PAKUAN, 2019)
The purpose of this study is to show Teacherâ€™s Organizational Citizenship Behavior (OCB) that can be improved by examining variables such as Transformational Leadership and Interpersonal Communication. This study uses a survey method with a correlational approach. The number of samples used was 104 people by using proportional random sampling technique. Based on the results of the study it is concluded that: (1) there is a very significant positive relationship between the Principal Transformational Leadership and Organizational Citizenship Behavior of teachers with a simple linear regression equation Å¶ = 99.53 + 0.32 X1 and the correlation coefficient value ry.1 = 0.417. The coefficient of determination r2y.1 = 0.174 means that the Transformational Leadership (X1) contributes to the teacher's Organizational Citizenship Behavior by 17.40%, (2) there is a very significant positive relationship between Interpersonal Communication with Organizational Citizenship Behavior teachers with simple linear regression equations Å¶ = 100.44 + 0.29 X2 and the correlation coefficient ry.2 = 0.349, and the coefficient of determination r2y.2 = 0.116 which means that the contribution of Interpersonal Communication (X2) to the Organizational Citizenship Behavior of the teacher is 19.60%, Â (3) there is a very significant positive relationship between Transformational Leadership and Interpersonal Communication together with the Organizational Citizenship Behavior of teachers with the multiple linear regression equation Å¶ = 77.25 +0.27 X1 +0.21 X2 and the correlation coefficient value ry.12 = 0.152. The coefficient of determination r2y.12 = 0.390 means that the Principal Transformational Leadership (X1) and Interpersonal Communication (X2) together contribute to the Organizational Citizenship Behavior of teachers (Y) by 15.20%.